PERSEBARAN PELAYAN KESEHATAN TINGKAT PERTAMA DI KABUPATEN SUKOHARJO TAHUN 2011 - Ronggowulan, Lintang (Pendidikan Geografi, 2013)
ABSTRACTThe purpose of this study was to find out distribution of Primary Health Care at Sukoharjo regency in 2011.This research uses descriptive qualitative research methods with spatial approach. This research used the accidental sampling. Purposive sampling is used to select a sample of respondents to be interviewed about the quality of service of Primary Health Care. Data collection techniques using observation, interview and documentation. The analysis technique used is the analysis of primary data, secondary data and cross tables.The results of this study are Primary Health Care in Sukoharjo totaling 67 units consisting of 12 Puskesmas and 55 Puskesmas Pembantu . Quality of Primary Health Care at Sukoharjo regency in 2011 consisted of Puskesmas in Sukoharjo consists of 4 centers with excellent quality, 7 health centers with good quality and 1health center with enough quality. Quality of Puskesmas Pembantu consists of 12 center with excellent quality, 35 health centers with good quality and 8 health centers with sufficient qualit. The visitor of Primary Health Care in Sukoharjo consisted of Puskesmas belonging to high class with the most number of visits to Puskesmas Kartasura is that 53,296 people (14.46%). Puskesmas Pembantu were included in the high-class with the most number of visits is a health center II Kartasura the 36,615 inhabitants (8.62 %). The level of accessibility in Sukoharjo in 2011 consisted of a wide range of leading health service consisting of waiter reach Puskesmas and Puskesmas Pembantu outreach , with each subdistrict in Sukoharjo Year 2011. The adequacy of the Primary Health Care that has been fulfilled is the District Tawangsar.Keywords :Distribution, Primary Health Care